Massive Open Online Courses for Africa by Africa - Oyo, Benedict; Kalema, Billy Mathias (International Review of Research in Open and Distributed Learning, 2014)
Africa is known for inadequate access to all sorts of human needs including health, education, food, shelter, transport, security, and energy. Before the emergence of massive open online courses (MOOCs), open access to higher education (HE) was exclusive of Africa. However, as a generally affordable method of post-secondary education delivery, MOOCs place the developing countries at the centre of universal access to HE. This paper provides the strategy for MOOC implementation in the context of limited resources in Africa. The strategy is clustered under five baseline requirements: national accredited MOOC curriculum, electronic content development, development of an online and offline eLearning platform, establishment and funding of MOOC coordination units at public HEIs, and establishment of MOOC access hubs at strategic locations. Emerging from this paper is the insight that a new era of universal access to HE in Africa is achievable through MOOCs only if initial requirements are met by the respective governments.